Accusing the accusers: Invective, identity, and “triangulated relations” in Plato’s Apology of Socrates (Nuntius Antiquus, 2024)
This paper discusses an aspect of rhetoric in Plato’s Apology of Socrates: invective, the modes that the defendant uses to attack, undermine the credentials, and diminish the credibility of his accusers, namely Meletus, Anytus, and Lycon (with side attacks also being hurled against others, including Aristophanes). “Accusing the accusers” encapsulates and refers succinctly to the use of invective on the principle that the best form of defence is attack. It is, specifically, examined how invective on the part of the defendant is articulated: what elements it is made up of, how it connects with and capitalizes on the general sociocultural context in classical Athens to deconstruct the identity of the accusers, and how useful it is in triangulating relations in court between the speaker, his opponent(s), and the audience – a technique that, as argued in scholarship, has tremendous potential to affect the verdict of the judges.